The Appearance of Good Luck: Aristotle’s Ethical Inquiry in Eudemian Ethics 8.2 - Wei, Yixin (Phronesis, 2025)
This paper argues that Aristotle in Eudemian Ethics (EE) 8.2 invalidates the question of whether good luck, understood as irrational but continuous success in performing virtuous actions, can produce happiness. The ‘lucky’ people in EE 8.2 possess what Aristotle elsewhere calls ‘natural virtue’. By attributing their success to nature and god instead of luck, he denies they have genuine good luck. This denial reveals that the question of whether such ‘good luck’ can lead to happiness is inherently misconceived. On this interpretation, the examination of good luck in the EE takes a significantly different approach than its counterpart in the Nicomachean Ethics (NE).